Profile of Ocular Trauma during COVID-19 Pandemic Lockdown at a Tertiary Center in Eastern Nepal - Chaudhary, Santosh; Shah, Sangeeta; Lavaju, Poonam; Ansari, Zahir; Shrestha, Chandra Bahadur; Badhu, Badri Prasad (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: Ocular injury is one of the most common causes of visual blindness worldwide. It is also an important cause of emergency hospital visits. We aimed to study the clinical profile of ocular trauma during COVID-19 pandemic lockdown.Methods: This cross-sectional study reviewed all the patients who presented with ocular trauma at B. P. Koirala Institute of Health Sciences between 1 April to 30 June 2020. Patient demographics, presenting complaint, duration of presentation, agents, place, settings, pattern, and management of ocular trauma were recorded and reviewed.Results: A total of 73 patients presented with ocular trauma during the study period. The mean age of patient was 33.96 ± 18.17 years. Males were more prone to trauma (male: female = 1.66:1). Most of the trauma occurred during household activities (n = 26, 35.6%). Students were the most vulnerable group (n = 26, 35.6%). The duration of presentation to the hospital (mean ± SD) was 1.77 ± 0.99 days . Eleven (15.1%) patients were blind due to trauma (visual acuity < 3/ 60). Blunt object was the main agent (n = 42, 57.5%) and closed globe injury (n = 50, 68.5%) was the main type of ocular trauma during the lockdown. Surgical intervention was required in 32.9% of patients and lid laceration repair (66.7%) was the surgery performed the most.Conclusion: Most of the patients suffered ocular trauma during household activities as outdoor activities were restricted during the lockdown period. Ocular trauma was predominant in the males and the students.